2014
DOI: 10.1371/journal.pone.0095533
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Relevance of Asthma Susceptibility with the Alteration of Integrin β 4 Expression

Abstract: Accumulated research has suggested the importance of the adhesion molecules modulation as therapeutic approach for bronchial asthma. Adhesion molecules expression alteration contributes to the pathogenesis of asthma. In order to probe the roles of expression imbalance of adhesion molecules in asthma pathogenesis, expression profiling of adhesion molecules was performed using cDNA microarray assay. The results showed that the expression pattern of adhesion molecules was altered in peripheral blood leucocytes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…By cDNA microarray assay, our previous work demonstrated that ITGB4 is downregulated in asthma airway epithelial cells with 4 variation sites in 5′ flanking region . ITGB4 is a traditional adhesion molecule that mediates the anchoring of airway epithelial cells to the basal membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By cDNA microarray assay, our previous work demonstrated that ITGB4 is downregulated in asthma airway epithelial cells with 4 variation sites in 5′ flanking region . ITGB4 is a traditional adhesion molecule that mediates the anchoring of airway epithelial cells to the basal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…As the airway epithelium is the first cellular barrier to external allergens, structural damage, and loss of function in these cells could alter airway inflammation reactions after allergic stress. Our previous work demonstrated that structural adhesion molecule integrin β4 (ITGB4) is downregulated in asthma airway epithelial cells with 4 variation sites in 5′ flanking region . ITGB4 is located at the basal surface of airway epithelial cells in hemidesmosomal structures that mediate the stable adhesion of epidermal cells to the underlying basement membrane component laminin‐5 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 2010 Provided evidences that ITGβ4 was involved in the structural integrity and functional homeostasis of airway epithelial cells (Liu et al, 2010b). The results of Zhou et al, 2008 andXiang et al, 2014, showed that the expressions of integrin β4 were down-regulated in asthma patients, and that it was associated with the variation in5'flanking region.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sheppard 2003 showed that integrinβ4 expression was clearly elevated after airway epithelialinjuryand could be detected in many cell types, which suggest that integrin β4 might be involved in the repair processes of airway epithelium (Sheppard 2003). Xiang et al, 2014 found thatmutations in 5̄ flanking region of integrin β4 gene result in reduced integrin β4 expression, and that it was related to increased risk of asthma (Xiang et al, 2014). ITGs are heterodimeric receptors that mediate cell adhesion, migration and tissue organization (Staunton et al, 2006) and might be a death factor in endothelial cells (Hiran et al, 2003).…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــ‬ ‫ـــــــmentioning
confidence: 99%
“…Integrins play important roles in the adhesion, tissue repair and microenvironment homeostasis of airway epithelial cells . Among these molecules, ITGB4 has been shown to decrease significantly in the airway epithelial cells of asthma patients with specific variant sites . By binding with basement membrane component laminin‐5, ITGB4 mediates the structural adhesion of airway epithelial cells to basal surface in hemi‐desmosome structure .…”
Section: Introductionmentioning
confidence: 99%